2024
DOI: 10.3390/neurosci5020007
|View full text |Cite
|
Sign up to set email alerts
|

“I Wouldn’t Even Know What to Ask for”: Patients’ and Caregivers’ Experiences of Psychological Support for Huntington’s Disease in Italy

Nicolò Zarotti,
Barbara D’Alessio,
Marta Scocchia
et al.

Abstract: People with Huntington’s disease (HD) often experience psychological difficulties linked with disease progression and the adjustment to living with a chronic condition, which are also frequently shared by their informal caregivers (e.g., partners). Although limited, the current literature on psychological care for people with HD shows that interventions have the potential to drive improvements in mental health and quality of life. However, the experience of accessing and receiving psychological support for HD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the context of HD care, integrating psychological services into treatment models can play a crucial role in achieving this goal. These integrated care models help alleviate the psychological burden associated with HD, not only improving patients’ well-being but also reducing healthcare costs [ 59 , 60 ]. The studies examined suggested that depression, anxiety, and neuropsychiatric symptoms significantly contribute to the risk of suicide in HD and require considerable attention from a clinical point of view [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of HD care, integrating psychological services into treatment models can play a crucial role in achieving this goal. These integrated care models help alleviate the psychological burden associated with HD, not only improving patients’ well-being but also reducing healthcare costs [ 59 , 60 ]. The studies examined suggested that depression, anxiety, and neuropsychiatric symptoms significantly contribute to the risk of suicide in HD and require considerable attention from a clinical point of view [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective HD treatment should not only focus on managing symptoms but also aim to improve the overall well-being of those affected. Patients are concerned with more than just their test results or symptom severity; they are deeply impacted by how HD affects their daily lives [ 60 ]. Recognizing the importance of mental health is crucial in shaping the outcomes of HD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations